Dependence of the conservation status of acid grasslands at the Pohorje and Kozjak on socioeconomic parameters - Karmen KETIŠ; Klemen ELER; Andrej UDOVČ; Franc BATIČ (Acta Agriculturae Slovenica)
Grassland habitats were studied on twenty farms on the area of the Radlje ob Dravi administration unit, in the transect from Kozjak to Pohorje at different altitudes. The aim of the study was to investigate how environmental and  socio-economic parameters influence the diversity of plant species and, consequently, the conservation of grassland on acid soils, which are rare in Slovenia and are therefore more protected. The socioeconomic structure of farms was studied on the basis of an inquiry carried out on farms. Part-time farms prevail; the average age of farmers is 56.5 years, and 30% of farmers has no education or just elementary school. The relationship among the environmental, socio-economic parameters and floristic structures of grasslands was studied using canonic-correspondence analysis. The impact of 16 parameters was analysed, of which six were determined not to be statistically significant. The occurrence of chosen plant species was analysed in relation to environmental and socioeconomic parameters. The efficiency of agro-environmental subsidies in relation to plant species diversity was evaluated. It was determined that the education and age of farmers influence the intensity of farming and consequently have an impact on the diversity of plants species and the conservation status of grasslands.